Circular economy in supply chain sustainability: From bibliometric analysis to conceptual model - Bahri, Mohammad Saiful; Handayani, Dwi Iryaning; Hudzafidah, Khusnik; Adnani, Kamila; Mahbub, Moh Mahbub (Center for Science and Technology, IAIN Surakarta, 2025)
This study aims to analyze research trends on the circular economy and supply chain sustainability using a bibliometric approach and to develop a conceptual model that can guide the implementation of circular economy practices. Data were obtained from the Scopus database and analyzed to identify publication trends, scientific contributions, and collaborations among researchers. The results show a significant increase in research related to the circular economy since 2020, especially in the manufacturing and technology sectors, with a primary focus on recycling, reuse, and remanufacturing as key elements of supply chain sustainability. The developed conceptual model emphasizes the importance of integrating technologies such as the Internet of Things (IoT), blockchain, and Big Data, alongside the Triple Bottom Line approach, that includes economic, environmental, and social aspects. Collaboration among stakeholders, governments, and consumers is also identified as an important factor in accelerating the adoption of the circular economy. This study contributes to the development of circular economy implementation strategies across various sectors and highlights future research opportunities, such as circular bioeconomy and green innovation. The proposed model is expected to serve as a guide for companies and policymakers in strengthening supply chain sustainability.